2014
DOI: 10.1021/jp4119502
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Concentration Quenching Mechanism in Gd2O3:Eu3+.

Abstract: Luminescence concentration quenching in Gd2O3:Eu(3+) nanocrystals results from strong interactions among O(2-) ions and Eu(3+) ions. Because all synthesized Gd2O3:Eu(3+) nanocrystals present the same cubic crystalline phase regardless of Eu(3+) concentration, it is possible to study the optical properties as a function of the dopant concentration. The emission intensities and lifetime curves for Gd2O3:Eu(3+) were analyzed by a simple rate equation model to study the interaction between the O(2-) ions and Eu(3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 27 publications
1
44
0
1
Order By: Relevance
“…The ratio between the electron dipole and the magnetic dipole is a measure of the site symmetry at which europium is situated. In addition, we can see other energy transitions of Eu 3þ corresponding to 5 D 0 / 7 F 0 near 585 nm and 5 D 0 / 7 F 3 near 628 nm (Chen et al, 2004;De la Rosa, Diaz-Torres, Salas, & Rodríguez, 2005;Jia et al, 2009;Liu, Hong, & Sun, 2004;Meza et al, 2014;Xu et al, 2008) in all the emission luminescence spectra. The 5 D 0 / 7 F 3 transition which is magnetic dipole transition remains independent from the chemical environment of dopant ions whereas the 5 D 0 / 7 F 2 transition which is electric dipole transition.…”
Section: Pl Excitation Spectramentioning
confidence: 84%
“…The ratio between the electron dipole and the magnetic dipole is a measure of the site symmetry at which europium is situated. In addition, we can see other energy transitions of Eu 3þ corresponding to 5 D 0 / 7 F 0 near 585 nm and 5 D 0 / 7 F 3 near 628 nm (Chen et al, 2004;De la Rosa, Diaz-Torres, Salas, & Rodríguez, 2005;Jia et al, 2009;Liu, Hong, & Sun, 2004;Meza et al, 2014;Xu et al, 2008) in all the emission luminescence spectra. The 5 D 0 / 7 F 3 transition which is magnetic dipole transition remains independent from the chemical environment of dopant ions whereas the 5 D 0 / 7 F 2 transition which is electric dipole transition.…”
Section: Pl Excitation Spectramentioning
confidence: 84%
“…As Fig. 7(c) shows, the emission intensity of the Eu 3+ ions increases with increasing concentration of Eu 3+ , reaches a maximum at 4 mol.% RE, and decreases thereafter (owing to the quenching effect) [76]. The critical quenching concentration of Eu 3+ is defined as the concentration at which the emission intensity begins to decrease.…”
Section: Insert Figurementioning
confidence: 93%
“…Goldys et al employed the hydrogen flame pyrolysis method to synthesize Gd 2 O 3 nanoparticles with size distribution from 2 nm to 300 nm [24]. Lanthanide ion-doped Gd(OH) 3 and Gd 2 O 3 have also been extensively prepared for applications regarding displays [16,[25][26][27] and fluorescence imaging [1,2,4]. Kim et al reported photoluminescence profile imaging of Eu (III)-doped Gd(OH) 3 and Gd 2 O 3 nanorods [9].…”
Section: Introductionmentioning
confidence: 99%